Histological Studies on the Caecum of Postnatal Guinea Pigs (Cavia porcellus) - Raja K; Rajathi S; Usha Kumary S; Archana K; Kumar K; Hemavathi N; Damini V (Indian Journal of Veterinary Anatomy, 2026)
The present histological study was conducted on the caecum of guinea pigs at different postnatal age groups. Microscopically, the caecal wall was composed of four layers namely the tunica mucosa, tunica sub mucosa, tunica muscularis and tunica serosa. The shape of the mucosal folds in the epithelium was short and stout like in 0–2-week- old guinea pigs, whereas they appeared tongue shaped in remaining age groups. The Lamina propria was composed of loose connective tissue with Crypts of Lieberkuhn. The tunica submucosa was composed predominantly of collagen and reticular fibres, with few elastic fibres mainly around the walls of the blood vessels. The tunica muscularis com- prised an inner circular and an outer longitudinal muscular layer. The mean height and width of the mucosal folds, the height of the columnar epithelial cells and the thickness of the tunica muscularis increased progressively with advanc- ing age in all the age groups studied.